CD59 deficiency presenting as polyneuropathy and Moyamoya syndrome with endothelial abnormalities of small brain vessels. (September 2018) - Klemann, Christian; Kirschner, Janbernd; Ammann, Sandra; Urbach, Horst; Moske-Eick, Olaf; Zieger, Barbara; Lorenz, Myriam Ricarda; Schwarz, Klaus; Doostkam, Soroush; Ehl, Stephan; Korinthenberg, Rudolf
Abstract: CD59 is involved in lymphocyte signal transduction and regulates complement-mediated cell lysis by inhibiting the membrane attack complex. In the cases reported so far, congenital isolated CD59 deficiency was associated with recurrent episodes of hemolytic anemia, peripheral neuropathy, and strokes. Here, we report on a patient from a consanguineous Turkish family, who had a first episode of hemolytic anemia at one month of age and presented at 14 months with acute Guillain-Barré syndrome (GBS). The child suffered repeated infection-triggered relapses leading to the diagnosis of chronic inflammatory demyelinating polyneuropathy (CIDP). Although partly steroid-responsive, the polyneuropathy failed to be stabilized by a number of immunosuppressive agents. At the age of 6 years, he developed acute hemiparesis and showed progressive stenosis of proximal cerebral arteries, evolving into Moyamoya syndrome (MMS) with recurrent infarctions leading to death at 8 years of age. Post-mortem genetic analysis revealed a pathogenic p.(Asp49Valfs*31) mutation in CD59. Re-analysis of brain biopsy specimens showed absent CD59 expression and severe endothelial damage. Whereas strokes are a known feature of CD59 deficiency, MMS has not previously been described in this condition. Therefore, we conclude that in MMS combined with hemolysis or neuropathy CD59 deficiency should be considered. Establishing the diagnosis and targeted therapy with eculizumab might have prevented the lethal course in our patient. Highlights: Congenital isolated CD59 deficiency leads torecurrent episodes of hemolytic anemia, peripheral neuropathy, and strokes. In this 4 th patient with thep.Asp49Valfs*31 mutation in CD59 reported, brain endothelium showed absent CD59 expression. Moyamoya syndrome developed while systemicvasculitis could be excluded. Targeted therapy against complement factor C5 with eculizumab might have prevented the lethal course in our patient.